Evaluation of kinetics and transport mechanism of solvents through natural rubber composites containing organically modified gadolinium oxide. (27th May 2016) - Sambhudevan, S.; Shankar, B.; Appukuttan, S.; Joseph, K.
Abstract : The solvent transport properties of the prepared composites were analysed using solvents of varying cohesive energy density and the effect of both modified as well as unmodified filler on the sorption and diffusion behaviour of NR vulcanisates has been investigated. It is found that the equilibrium uptake decreases with increase in filler content, as anticipated owing to the restrictions offered by the filler for solvents to diffuse into the polymer matrix. The mechanism of transport in natural rubber composites was carefully tracked and it was found to exhibit an anomalous mode of solvent transport where the polymer relaxation is in par with the rate of diffusion. Theoretical modelling of the swelling parameters was done and the results were found to be in agreement with existing models. The excellent swelling resistance coupled with the simultaneous improvement in mechanical properties would definitely pave way for the utilisation of these composites as barrier membranes.